Foreign Language Teaching with MOOCS: Comparison of Germany, France and Turkey - Özge Karacadal (Pamukkale Üniversitesi Eğitim Fakültesi Dergisi, 2018)
In this study, the term of ‘Massive Open Online Courses’ (MOOCs), which is one of the technological progresses in the domain of education in recent years was observed in the context of foreign language teaching. As the Massive Online Open Courses are free of charge and taken online through websites, they have many advantages for learners. They also have the characteristic of promoting the lifelong learning. In this research that was carried out with comparative and descriptive methods, the MOOC platforms in Germany and France, which are two of the leading countries in Europe, were presented with the aim of providing a contribution to the courses of foreign language teaching practices in Turkey. Besides, information about these courses in the countries was given. Then, addressing the MOOC platforms in Turkey and the courses in these platforms, the courses in the related European countries were compared to the ones existing in Turkey. With this comparison, the similarities and differences between the countries were identified and Turkey’s deficiencies at this point were revealed. To overcome the deficiencies in the online foreign language courses in Turkey, suggestions were offered considering the ones in Germany and France.